Do Past Experience and Group Heterogeneity Matter to Consumer Preferences? Evidence From a Choice Experiment in Urban China - Liu, Ruifeng; Liang, Fei; Heng, Yan; Gao, Zhifeng; Snell, Heather Arielle; Rae, Allan; Ma, Hengyun (Frontiers in Psychology, 2022)
This study uses a discrete choice experiment to examine consumers’ preferences for Fuji apple product attributes and willingness to pay (WTP) estimates for consumers in six cities of China. We estimate preference heterogeneity by linking the stated preference choice data with consumers’ past experience and socioeconomic characteristics in the latent class model. The empirical results show that, first, the past experience variables are crucial in explaining consumer preferences and WTP. Second, three classes, i.e., certification-oriented, price and origin-oriented, and not interested are identified. Furthermore, the same type of Fuji apple attribute does not appeal to every respondent. Third, our results indicate the heterogeneity of preferences across different classes of respondents, as well as differences in WTP for Fuji apples.